Anticipation and visual search in elite sport : the effects of anxiety, training and expertise - Alder, D. B. (Liverpool John Moores University, 2014)
The aim of this thesis was to examine the influence of high-anxiety, training and expertise-level on perceptual-cognitive skills in the sport of badminton. First, the coupling between observed badminton serves, visual search behaviour and anticipation judgements of athletes ranging in expertise was investigated. Expert players produced more accurate anticipation judgements compared to novice athletes. Experts fixated vision upon body areas containing the discriminating kinematic information between serve- types more frequently and for a longer duration compared to novice players. A subsequent case-study highlighted the relationship between expertise, visual search and anticipation judgement extended to a world-class athlete. Second, the role of skill level in mediating the effects of high anxiety on anticipation and the capacity to allocate attentional resources to a secondary task was examined through high- and low-anxiety conditions. Skilled players made more accurate anticipation judgements compared to their novice counterparts, regardless of anxiety conditions. High-anxiety resulted in a decrease in secondary task performance for the novice, but not the skilled group, when compared to low-anxiety. Finding demonstrates that skilled athletes can effectively allocate attentional resources during performance, leading to the effects of anxiety being negated, whereas novices cannot. Third, a perceptual-cognitive intervention consisting of simulation training under high-anxiety conditions led to greater anticipation performance under high-anxiety and field-based conditions compared to pre-test and training under low-anxiety conditions. Overall, expert athletes make superior anticipation judgements due to different visual search behaviours and attentional resources, all of which are robust to high anxiety, when compared to lesser-skilled players, with these abilities being trainable.